FACTORS INFLUENCING PHARMACIST KNOWLEGDE, ATTITUDE OF COMMUNICATION AND PERCEPTIONS OF COLLABORATION WITH HEALTH PROFESSIONAL IN THE IMPLEMENTATION OF MONITORING IN INPATIENTS - MUTMAINAH, NURUL; HAJMA, LILLA P. A.; ELIYAH; ASTUTI, NINA D.; SASKIA, ADINDA T. P.; HERIYAWATI, NURFITRIYANA (International Journal of Applied Pharmaceutics, 2025)
Objective: In health services, interprofessional collaboration is needed because no single profession can meet patient needs. Good quality health services depend on professionals working together in interprofessional teams. This research aims to determine the factors that influence pharmacists' communication with other health profesional as well as pharmacists' perceptions of collaboration. Method: This research uses a quantitative, non-experimental research design with a cross-sectional approach. The research subjects were pharmacists who worked in hospitals and do a collaboration with health professionals. The instrument is a questionnaire, consisting of three parts: respondent demographics, measuring pharmacists' knowledge and attitudes about communication, Collaborative Practice Assessment Tool (CPAT) perception questionnaire. Knowledge items were tested for validity using the content validity method using expert judgment. Attitude items were tested for content validity using the Pearson Product Moment correlation coefficient, followed by Cronbach's Alpha reliability test. CPAT questionnaire scores were calculated using a 5-point likert scale and analyzed descriptively. Data were analyzed with chi-square and continued with multiple regretion analysis tests for variables that met the requirements. Result: The results found that 94.59% of respondents had knowledge in the good category, 5.41% in the sufficient category. Meanwhile, 51.35% of respondents had a positive attitude towards collaborative practices and 48.65% had a negative attitude. The results of measuring perceptions found that respondents had a positive perception of interprofessional collaboration practices, with the best perception in the domain of general relationship and the worst perception in the domain of decision making and conflict management. Conclution: From this research we can conclude that the factors that influence knowledge and attitudes are gender, age, and level of education. This study may be underpowered to detect effects of gender, age, education level, salary and work experience towards perception.